A Systematic Review of Access Control Models: Background, Existing Research, and Challenges - Nastaran Farhadighalati; Luis A. Estrada-Jimenez; Sanaz Nikghadam-Hojjati; Jose Barata (IEEE Access)
Data security has become paramount, especially with the exponential growth of data, the rise of cyber threats, and the increasing prevalence of remote work. Data confidentiality, integrity, and availability are crucial, particularly in sensitive domains like healthcare and cloud computing. While robust access control (AC) is essential, it must be balanced with maintaining operational efficiency. In access control models, there is a general lack of a comprehensive cross-domain overview, insufficient focus on evolving access control requirements, and inadequate analysis of challenges and issues. This paper comprehensively analyzes access control models (ACMs) through a two-pronged approach. First, we conduct a Narrative Literature Review(NLR) to classify traditional ACMs, evaluating their security strengths and weaknesses and compatible security protocols. Second, we perform a Systematic Literature Review (SLR) of emerging ACMs developed over the past decade across various domains. This systematic review has three primary objectives: (1) to introduce and analyze these emerging ACMs, (2) to present their current technological status, and (3) to identify key challenges and promising research directions. By combining these approaches, this paper offers a comprehensive overviewofACMapplications and techniques, identifies existing challenges, and explores future research directions to guide advancements in access control.